Giant Calculus in the Ureteropelvic Junction: A Case Report - Costa, Luis Domingos R.; Alvarenga, Raffael M.; Oliveira, Yvis E. De Jesus De; Soares, Fernanda T.; Junior, Geraldo B Silva; Daher, Elizabeth F. (Journal of Medicine, 2014)
Urinary lithiasis is an affection of high social impact associated with high costs. Its incidence varies from 1 to 15% in the general population and has a recurrence chance of 26-50%. We report one rare case of giant ureteral calculus in the ureteropelvic junction in a patient with complaints of left lumbar pain and recurrent urinary tract infection diagnosed in the outpatients Urology clinics. Antibioticotherapy was instituted and complementary tests were done. The abdomen x-ray showed a large opacity in the left kidney topography, and the computed tomography evidenced a giant left ureteral calculus associated with a large ureteropelvic junction dilation and grade III hydronephrosis. An ureterolitothomy was performed and evidenced a calculus of 9.5x6.5cm and weighting 347g. The patient became well after the surgery, and a pyelogram evidenced dilation of both caliceal groups and left ureter, without any calculus. Urinary lithiasis should be early diagnosed and treated in order to avoid severe complications as the presented here. DOI: http://dx.doi.org/10.3329/jom.v15i1.19884 J Medicine 2014; 15: 91-93